Membangun Psychological Capital Melalui Pelatihan dalam Keterampilan Sosial, Keterampilan Komunikasi, dan Pengelolaan Konflik: Studi Pilot di Indonesia - Lukas Neuwirth; Triana Kesuma Dewi (Universitas Airlangga, 2025)
Social competences are crucial for personal and professional success as well as overall well-being. Research suggests these skills may also enhance Psychological Capital (PsyCap), a construct comprising self-efficacy, resilience, hope, and optimism, which itself is linked to various positive life and success outcomes. However, many PsyCap trainings combine social competence training elements with other interventions, making it unclear whether specific training alone contributes to PsyCap development. To address this, a two-day social competences, communication and conflict management (SCCCM) training was culturally adapted using a formative pre-test and pilot-test with Indonesian psychology students in a mixed-method, non-randomized quasi-experimental control group design (N=27). Results indicate notable improvements in PsyCap, flourishing, and life satisfaction within the test group, suggesting that improved social and communication competence may independently foster PsyCap. However, this study suffers major methodological limitations and further research with larger samples is needed to confirm these findings and explore underlying mechanisms.